2013
DOI: 10.1002/ange.201304182
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophenoxylation of Alkynes by Cooperative Gold Catalysis

Abstract: Zweifach: Die Titelmethode liefert Arylvinylether in hohen Ausbeuten, in kurzer Reaktionszeit, mit Z‐Stereospezifität und guten Regioselektivitäten. Einblicke in den Reaktionsmechanismus betonen die Rolle von [{Au(NHC)}2(μ‐OH)][BF4] (NHC=N‐heterocyclisches Carben) als Lewis‐Säure [Au(NHC)][BF4] und als Brønsted‐Base [Au(NHC)(OH)] – zwei Goldeinheiten, die synergistisch wirken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…Catalyst 1 gave a slightly higher yield of the addition product, but 7 was more selective. The regioselectivity of the reaction using our arylgold precatalysts is the opposite of what Sahoo found using his catalyst system [1] and is similar to the regioselectivity found by Nolan using his hydroxide bridged precatalysts [5]. …”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Catalyst 1 gave a slightly higher yield of the addition product, but 7 was more selective. The regioselectivity of the reaction using our arylgold precatalysts is the opposite of what Sahoo found using his catalyst system [1] and is similar to the regioselectivity found by Nolan using his hydroxide bridged precatalysts [5]. …”
Section: Resultssupporting
confidence: 77%
“…The use of gold compounds to promote hydroelementation reactions has grown tremendously over the past few years [15]. Using this approach, a host of different organic substrates have been successfully functionalized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a collaboration, Bergman, Raymond and Toste used the anionic Ga 4 L 6 cage to encapsulate the gold phosphine complex [Au(PMe 3 )Br]. [41] As the cage encapsulates cationic species, the bromide ion dissociates upon inclusion, leaving the more active complex [Au(PMe 3 )] + inside the cage. This encapsulated species catalyzed the intramolecular hydroalkoxylation of an allenol in 48 % yield in 18 hours, whereas the non-encapsulated [Au(PMe 3 )Br] gave only 11 % yield after this time (Scheme 6).…”
Section: L 6 Cagesmentioning
confidence: 99%
“…We have recently reported that a digold catalyst, [{Au(IPr)} 2 -(m-OH)][BF 4 ] (1), could mediate the addition of phenols to un-activated internal alkynes through a dual activation mechanism. [6] This reaction possesses several advantages compared to the previous state-of-the-art, such as the use of milder reaction conditions, lower catalyst loadings, higher turnover numbers (TON) and turnover frequencies (TOF). We continue to be interested in the development of highly efficient and environmentally benign catalytic methodologies for the synthesis of organic molecules; therefore, we sought to combine the advantages offered by an eco-friendly solvent-free protocol, and the atom-and step-economy of sequential strategies.…”
mentioning
confidence: 99%